ABSTRACT Productivity improvement is an essential effort to achieve the optimal utilization of the resoures, particularly in production on the assembly line of soy sauce (soy filling) in PT X. The productivity improvement is based on measuring the OEE (Overall Equipment Effectiveness). OEE is a measurement methods of the production machine effectiveness that involves measurement of the availability rate, performance rate, and quality rate. Through measurement of OEE​​, the potential equipm - Taufik Djatna dan Ida Bagus Dharma Yoga santosa (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT   Productivity improvement is an essential effort  to achieve the optimal utilization of the resoures, particularly in production on the assembly line  of soy sauce (soy filling) in  PT X.  The productivity improvement is based on measuring the OEE (Overall Equipment Effectiveness). OEE is a measurement methods of the production machine effectiveness that involves measurement of the availability rate, performance rate, and quality rate. Through measurement of OEE​​, the potential equipment utilization, identify bottlenecks and track the lossess were monitored. Results of the OEE measurement on assembly line in PT. X indicate a lower level  than optimal results so that the improvement is required  to improve the competitiveness of enterprises. A quantitative model of Particle Swarm Optimization (PSO)  was  ​​modified to improve the productivity and to reduce the productivity cost.   Keywords: productivity improvement, lean production, OEE, Particle Swarm Optimization